Impact of Gadget Addicts on Family Harmony Perspective of Islamic Law - suryaningsih (NUSANTARA: Journal Of Law Studies, 2022)
This research examines "the impact of gadget addicts on family harmony from the perspective of Islamic law". This type of research is field research. The research informants were 20 heads of families out of 633 heads of families in Riak Siabun village. The 20 heads of families are believed to be gadget addicts. The author also interviewed several community shops, such as the Head of the Riak Siabun village, the Akbar Study Chairperson and the Regional Representatives Council Chairperson. The study results show that the impact on the family of gadget addicts in the village is the loss of mutual trust between family members, not having time with family, forgetting responsibilities in worship and having a difficult economy and the occurrence of infidelity. The best solution to overcome this is by deliberation among family members by bringing in mediators from religious leaders and the village government